Strategy Formulation of PT. Tunggal Sejati Kencana (Case study : Pekanbaru Logistic Center in Pekanbaru, Riau) - Anugrah Wangsa, Airin; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2016)
Abstract- The formulation process to create a business strategy for PLC started from external and internal environment scanning those are be done by several methods such as : PESTEL Analysis, SWOT analysis, Porter’s Five Forces Analysis, Resources Based View Analysis, Value Chain Analysis, Current Corporate and Business Level Analysis, EFAS Matrix, IFAS Matrix, IE Matrix, TOWS Analysis, Grand Strategy Matrix, Ansoff Growth Matrix. Next step is to integrate cross functional with capabilities and positioning. To take action in the proposed strategy must be aligned with the company’s vision, mission and values. Based on the result of analysis, the corporate strategy that can be implemented by PLC Warehouse based on orientation toward growth strategy, it aims to create value for the shareholders, customers and also citizens. Besides, to increase the revenue, should do the market penetration by using differentiation as the best business strategy. Market penetration and differentiation focused strategies are also supported with functional strategies that consists of marketing, research and development, and human resource. New strategies that should be pursued by the company includes : competence and leadership personnel, customer relationship management, marketing by digital media, cost control, develop capabilities, technological warehousing system. In conclusion, PT. TSK currently has competitive advantage in the warehousing industry but the company also needs to prepare for the future treats and opportunities. The company should align their strategy from corporate level and business level strategy to achieve the goals in the future. Keywords: Business Strategy, Corporate Level Strategy, Competitive Advantage, Strategic Management, Warehousing Business Industry